Identification of RB1 germ-line mutations in patients with retinoblastoma / Kavimalar A/P Renganathan - Renganathan, Kavimalar (2014)
Background: Retinoblastoma (RB1; OMIM#180200) is the most common intraocular tumor in early childhood. The malignancy mainly affects children under five years of age, with a prevalence of 1:15,000 to 1:20,000. RB1 or retinoblastoma susceptibility gene is the gene associated with retinoblastoma and is located on chromosome 13q14.2. The whole coding region of RB1 has 27 exons. The gene encodes a tumor suppressor, the retinoblastoma protein (pRB). Retinoblastoma develops when both alleles of the tumor suppressor gene are inactivated by loss-of-function mutations. The hereditary predisposition to the disease is caused by germ-line mutations in RB1. Since RB1 is a tumor suppressor gene, the survivors of hereditary retinoblastoma also possess high risk of developing non-ocular cancers in their subsequent life. The identification of oncogenic germ-line mutations in the RB1 gene of patients with retinoblastoma is significant for genetic counselling. There are very few reports on RB1 mutations identified in Malaysian patients with retinoblastoma although several studies have been published on the prevalence and clinical features of the disease. Aims: This was a hospital-based retrospective study to screen the entire coding region of RB1 for de novo germ-line mutations in patients with no reported family history of retinoblastoma. Methods: This study involved a cohort of six unrelated cases of sporadic retinoblastoma with different laterality of disease: three unilateral and three bilateral cases. Genomic DNA was extracted from peripheral blood of healthy control and patients with retinoblastoma. Polymerase chain reaction (PCR) was carried out to amplify the 27 exons of RB1. The purified PCR amplicons were then subjected to bidirectional DNA sequencing. Sequence data was compared with RB1 DNA sequence iv of two healthy controls of Chinese and Malay ethnicity and RB1 reference sequence (GenBank accession no. L11910.1) to identify mutations. This exon-by-exon mutation analysis was conducted in silico. Results: Analysis of DNA from blood leukocytes revealed heterozygous and heritable mutations in the RB1 gene of two patients with bilateral retinoblastoma. The mutations were identical single base substitutions which caused a C to T transition: g.162237C>T. The nonsense mutation which was found in exon 23 changed codon 787 from wild-type CGA to mutant TGA (p.Arg787X), resulting in a premature stop codon. All three patients with unilateral retinoblastoma did not show any mutation in the RB1 gene. Conclusions: The findings proved that the mutations detected in DNA extracted from blood of patients were constitutional. The identified mutations were de novo mutations as both parents of respective patients lacked the abovementioned mutation in their RB1 gene. The experiment results were consistent with past reports that patients with bilateral retinoblastoma usually harbour germ-line mutations in the RB1 gene. Based on the study result, exon 23 and CGA codons are apparently more frequent mutational targets and should be initially screened in Malaysian patients with retinoblastoma though no mutation hot spots have been reported in RB1 gene thus far. However, further studies with extended sample size would be needed to evaluate and establish a protocol for routine RB1 mutation analysis.